Selected Properties of Input Stock Material for the Production of Thin-Walled Cylindrical Products by Cold Flow Forming - Marek BURDEK; Jarosław MARCISZ; Jerzy STĘPIEŃ; Ewelina SKOWRON; Zbigniew HAJDAK; Bogumiła KOWALIK; Józef KRÓL (Problemy Mechatroniki, 2019)
This paper presents test results for the steel grade 15HGMV metallurgical purity, microstructure, method of production and effect on the mechanical performance of the input stock material for calibre 227 mm missile motor casings manufactured by cold flow forming. The reference product for the determination of preliminary design criteria of missile casings of the higher calibre were calibre 122 mm missiles manufactured in Poland. The final mechanical properties of the casings are a cumulative effect of quenching and tempering and strain hardening during cold flow forming. The research and industrial practice carried out so far have demonstrated that the production process of a Feniks missile (with a 1.5 mm thick casing wall) requires steel grades of extremely high purity. This steel grade is manufactured by VAD (Vacuum Arc Degassing) melting, followed by ESR (ElectroSlag Remelting) or, alternatively by melting and casting in vacuum oven. The content of hard and non-deformable non-metallic inclusions such as oxides is critical to the success of cold flow forming. The cal. 227 mm missile casings feature walls approximately 2.5 mm thick and produced by cold flow forming from a quenched and tempered intermediate product. New material specifications should be developed for this reason to enable correct cold flow forming and contribute to a significant improvement in the cost efficiency of manufacturing. The investigations covered herein were guided by an assumption that the thicker wall sections might make the material specifications applicable to lower-calibre missiles to restrictive and obsolete about cal. 227 missiles. After initial laboratory tests, this hypothesis will be verified in industrial experiments on the production of prototype missile casings from input stock materials varying in metallurgical purity.